Analisis Pelayanan Administrasi Kependudukan Pada Dinas Kependudukan Dan Pencatatan Sipil Provinsi Sumatera Utara - Arya Duta Permana Pane; Zainarti Zainarti (LPPM Universitas Labuhanbatu, 2022)
This research was conducted at the Population and Civil Registration Office of North Sumatra Province. The purpose of this research is to find out the Population Administration Service at the Population and Civil Registration Office of North Sumatra Province. This research is motivated by the number of community complaints against the Population Administration service at the Population and Civil Registration Office of North Sumatra Province. The author conducted this study to find out the services of the Population Administration at the Kampar Regency Population and Civil Registration Office as well as obstacles in the implementation of population administration services at the North Sumatra Population and Civil Registration Office.